Biuletyn Informacyjny "Obozu" . no. 12, 1985 - Ananicz, Andrzej ("Obóz", 1985)
Creation and circulation: In 1984-1988 publication for internal use of editors of independent periodicals. From issue no. 40(3.11.1988) published for the wider audience.